ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETIMPANGAN PENDAPATAN DI KABUPATEN DAN KOTA SE-JAWA TIMUR PADA TAHUN 2011-2019 - Bhagaskara, Andhika (Journal of Development Economic and Social Studies, 2023)
There has been high economic growth in East Java Province, as evidenced by a decrease in the Gini Ratio. To reduce income inequality, there is a need for strengthening wage policy systems and equitable government expenditures, as well as investment in sectors that are still lagging behind. Additionally, access to education, healthcare, and job creation also need to be reinforced to reduce the disparity between districts and cities in East Java. This study used panel data regression analysis to analyze the influence of independent variables such as economic growth rate, minimum wage, working population, human development index, government expenditures, and investment on the Gini Ratio. The results of the study indicate that the economic growth rate does not have a significant impact on the Gini Ratio, while minimum wage, human development index, government expenditures, and investment have a significant influence on the Gini Ratio, with a negative impact on minimum wage and investment, and a positive impact on the human development index and government expenditures. However, the variable of the working population does not have a significant influence on the Gini Ratio.